A UNIQUE FINDING OF ZIRCON INTO BADDELEYITE TRANSFORMATION (THE ICHETJU ORE OCCURRENCE, THE MIDDLE TIMAN) - S. G. Skublov; A. O. Krasotkina; A. B. Makeyev; O. L. Galankina; A. E. Melnik (Известия высших учебных заведений: Геология и разведка)
Findings of the growth relationships between baddeleyite and zircon are rare, due to significant differences in the formation conditions of the minerals. A reaction replacement (partial to complete) of baddeleyite by zircon is possible during metamorphism accompanied by the interaction with high-Si fluids. The opposite situation, when zircon is replaced by baddeleyite, is extremely rare in the nature. Transformation of zircon from polymineral (compound) ore occurrence Ichetju (the Middle Timan) with the formation of microaggregates of baddeleyite, ratile and florencite has been found out. The size of the largest segregations of baddeleyite does not exceed 10 microns in diameter. Microaggregates are unevenly related to the rim of zircon with a thickness of 10 to 50 rfn, voids and cracks across the grain. Altered zircon rim (a mixture of newly formed minerals) is characterized by sharply increased composition of REE (especially LREE), Y, Nb, Ca, Ti. The composition of Th and U also increases. An overview of the experimental studies on the reaction between zircon and baddeleyite and single natural analogues allows to make a conclusion that the most likely mechanism of the transformation of zircon from ore occurrence Ichetju to baddeleyite (intergrowth with ratile and florencite) is due to the effect of interaction of primary zircon with high-temperature (higher than 500—600°C) alkaline fluids transporting HFSE (REE, Y, Nb, Ti). This is indirectly confirmed by the findings of zircon with anomalous high composition of Y and REE up to 100000 and 70000 ppm respectively.